Colonization of the streptomycin-treated mouse large intestine by a human fecal Escherichia coli strain: role of adhesion to mucosal receptors. - Wadolkowski, E A (1988)
Escherichia coli F-18, a normal fecal isolate, was previously shown to be an excellent colonizer of the streptomycin-treated CD-1 mouse large intestine, whereas E. coli F-18col-, a derivative of E. coli F-18 that no longer makes the E. coli F-18 colicin, was shown to be a poor mouse colonizer. It was also shown that E. coli F-18 bound two to three times more soluble colonic mucus protein than did E. coli F-18col- and that a major receptor in CD-1 mouse colonic mucus was a 50.5-kilodalton glycoprotein. In the present investigation, an additional E. coli F-18 colonic mucus glycoprotein receptor (66 kilodaltons) and three cecal mucus glycoprotein receptors (94, 73, and 66 kilodaltons) were identified. Numerous colonic and cecal brush border protein receptors specific for E. coli F-18 were also identified. Furthermore, E. coli F-18col- was found to bind to the same mucus and brush border receptors as E. coli F-18, although to a far lesser extent. Adhesion of both E. coli F-18 and F-18col- was inhibited by D-mannose and alpha-methyl-D-mannoside, and both strains were shown to bind specifically to the mannose moiety of a mannose-bovine serum albumin glycoconjugate, although again E. coli F-18col- bound to a lesser extent. Finally, both E. coli F-18 and F-18col- were shown to be piliated. The possible role of pilus mediated adhesion in E. coli F-18 colonization of the streptomycin-treated mouse large intestine is discussed.